A modified hierarchical production planning system for make-to-order integrated with MRP - Kanlı, Sertaç (My University, 1996)
unknown
Keywords: Genel yönetim; ÜRETİM PLANLAMASI; Üretim yönetimi; ÜRETİM YÖNETİMİ